Ocean environmental management : Primer on the role of the Oceans and Hoe to Mountain Their Contributions to Life on earth - Frankel, Ernst G. (PTR Prentice Hall, 1995)
Dumping ... oil spills ... Beach erosion - the need for ocean environmental management is finally being recognized as a major concern. This timely volume explains the causes of, and problems introduced by, ocean pollution. Author Ernst G. Frankel presents some of the preventative and mitigating methods available, evaluates regulations and agreements promulgated to control ocean environmental impacts, and suggests approaches for the more effective management of the ocean environment.